A Systematic Review of the Socio-Economic Impact of Integrated Halal Assurance Systems on Microfarm Sustainability in Southeast Asia - Gunawati, Dita Novarina; Amalta, Luky; Damayanti, Cindy Audina; Puspitasari, Cesaria Fitri (CV. Komunitas Dunia Peternakan, 2025)
The global halal industry is experiencing exponential growth with a market value of trillions of dollars, creating significant economic opportunities for Southeast Asian countries with large Muslim populations. The micro-livestock sector has unique characteristics that require a specialized approach in the implementation of an integrated halal assurance system, given limited resources, technical capacity and access to technology. The complexity of implementation presents multidimensional challenges covering technical, economic, social and regulatory aspects that require comprehensive analysis to understand the socio-economic impact on the sustainability of micro farms1. This study aims to analyze the socio-economic impact of implementing an integrated halal assurance system on the sustainability of micro livestock enterprises in Southeast Asia through an integrated legal and business perspective. Systematic literature review using PRISMA guidelines with searches through Google Scholar and Scopus for the period 2020-2025. Inclusion criteria included studies of halal assurance system implementation on Southeast Asian micro farms, socio-economic impact analysis, and integration of legal-business perspectives. Quality assessment using the Mixed Methods Appraisal Tool (MMAT) with systematic data extraction using Microsoft Excel 2021. Of the 321 articles identified, 7 high-quality studies were included with a selectivity rate of 2.2%. The findings show variations in implementation approaches between countries: Indonesia with Law No. 33/2014 and SEHATI program, Malaysia through JAKIM with MS 1500:2019 standard, Singapore via MUIS with strict supervision. Positive social impacts include increased social acceptance, empowerment of women and minority groups, and establishment of collaborative networks such as halal cooperatives. Significant economic impacts include increased consumer confidence, wider market access, and product competitiveness with premium prices of up to IDR 37,500/kg for certified products. Integration of legal-business perspectives creates synergy through ASEAN regulatory harmonization, blockchain technology, and multi-stakeholder collaboration. The implementation of an integrated halal assurance system has a transformative impact on the sustainability of Southeast Asian micro livestock businesses, strengthening the regional halal economy and contributing to the Sustainable Development Goals.